Frontispiece: Spin Ice‐like Magnetic Relaxation of a Two‐dimensional Network based on Manganese(III) Salen‐type Single‐Molecule Magnets. Issue 49 (24th November 2020) - Kachi‐Terajima, Chihiro; Eiba, Tasuku; Ishii, Rikako; Miyasaka, Hitoshi; Kodama, Yuta; Saito, Toshiaki
Abstract : Single‐Molecule Magnets Spin ice‐like magnetic relaxation is found in Mn III salen‐type single‐molecule magnets. In their Research Article on page 22048, C. Kachi‐Terajima et al. demonstrate that the spin ice‐like behavior is a consequence of the competition between ferromagnetic interaction and local magnetic anisotropies.